Countering detector manipulation attacks in quantum communication through detector self-testing - Lijiong Shen; Christian Kurtsiefer (APL Photonics)
In practical quantum key distribution systems, imperfect physical devices open security loopholes that challenge the core promise of this technology. Apart from various side channels, a vulnerability of single-photon detectors to blinding attacks has been one of the biggest concerns and has been addressed both by technical means as well as advanced protocols. In this work, we present a countermeasure against such attacks based on self-testing of detectors to confirm their intended operation without relying on specific aspects of their inner working and to reveal any manipulation attempts. We experimentally demonstrate this countermeasure with a typical InGaAs avalanche photodetector, but the scheme can be easily implemented with any single photon detector.